2004
DOI: 10.1109/tmc.2004.26
|View full text |Cite
|
Sign up to set email alerts
|

Purposeful mobility for relaying and surveillance in mobile ad hoc sensor networks

Abstract: Abstract-In this paper, we consider a mobile ad hoc sensor network. The mobility of the sensor nodes is designed with the cost of communication and mobility in mind along with consideration of the possible scanning tasks of the nodes. Our mobility algorithm is developed in the context of a distributed system where, for any single mobile node, only local information about associated energy costs is known. We use a distributed simulated annealing framework to govern the motion of the nodes and prove that, in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 16 publications
0
53
0
Order By: Relevance
“…Controlled movement generally consists of mobile devices in the network and moving to specified destinations with defined mobility patterns for specific objectives. The receiver node can adapt its route to achieve more efficient coverage management [16][17][18], energy composition reduction [19,20], transport layer parameters' improvement [21,22], etc. Controlling the device's movements offers new possibilities to improve the data collection efficiency, or optimize the network topology for different type of objectives as the above referenced works show [23].…”
Section: Data Gatheringmentioning
confidence: 99%
“…Controlled movement generally consists of mobile devices in the network and moving to specified destinations with defined mobility patterns for specific objectives. The receiver node can adapt its route to achieve more efficient coverage management [16][17][18], energy composition reduction [19,20], transport layer parameters' improvement [21,22], etc. Controlling the device's movements offers new possibilities to improve the data collection efficiency, or optimize the network topology for different type of objectives as the above referenced works show [23].…”
Section: Data Gatheringmentioning
confidence: 99%
“…In mobile sensor networks, however, these issues are complicated due to the changing topology, typically resulting in a node being disconnected, the network becoming partitioned, or loss of sensing coverage in some regions. In addition, the mechanical energy consumption due to node mobility is generally higher than the energy required for sensing, communication, and computation [20], [24].…”
Section: Related Prior Workmentioning
confidence: 99%
“…The control mobility is achieved by setting rules based on where the mobile element goes as well as how long it is expected to take. Recently, in [24], Rao and Kesidis have shown that purposeful mobility can be used to achieve energy savings for routing in the sense of an amortized cost measure. It is also shown in [19] that mobility is helpful for maintaining sensing coverage for both static and mobile targets, particularly when the number of nodes is not sufficient for covering the complete area.…”
Section: Related Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In a real time setting mobility can be used to facilitate network connectivity and saving communication energy spent between sensor nodes and data repository. Rao et al [25] propose a communal-mission-oriented mobility to decide where to move a node so that it can perform either of the two tasks, that is, local scans (checking for uncovered regions) or data forwarding better. They have developed distributed mobility algorithms to support high priority tracking traffic (detailed information on tracked targets) by moving scanning nodes to route latency critical tracking traffic.…”
Section: Leveraging Node Mobility For Routingmentioning
confidence: 99%